The Washback Effect of The English National Examination Toward English Teachers, Students, Stakeholders and Parents - Asep Dadi; Karnedi Karnedi; Andang Saehu (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This research was conducted to measure the washback effect on students, English teachers, stakeholders, and parents of students from the implementation of the National Examination. This research study is a qualitative research design; Data collection techniques in this study were interviews and questionnaires. The results of this study are that the English National Examination have a negative effect rather than a positive effect. The method teachers have used in the teaching and learning process, focusing on preparation for the English National Examination, tends to emphasize reading skills and override other English skills. Then students facing the National Examination tend to be divided into several groups; some relax without studying, but some students feel worried and afraid of being unable to pass the National Examination. National Examination activities for schools certainly impact many things, especially facilities and infrastructure that must be prepared as well as possible by schools so that the National Examination can run well. For parents of students, National Examination activities also affect the pattern of education at home; parents must provide more understanding and advice to their children to study more seriously.